2012
DOI: 10.1017/s002531541200166x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental and longline fishing operational variables on the presence of killer whales (Orcinus orca) in south-western Atlantic

Abstract: Killer whale (Orcinus orca) is frequently encountered in coastal and high productive pelagic waters, near the shelf break. In the south-western Atlantic Ocean, spatial and temporal occurrence patterns are poorly known. However, the monitoring of the interaction between killer whales and longline fishery suggests that the species is frequent in this region. We analysed the killer whale presence within the Uruguayan pelagic longline fishing zone. Data were collected from 1996 to 2007, during 2189 fishing events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Our modelling of killer whale relative density indicated a positive relationship with maximum Chl a concentration, consistent with the known physiology of other members of the Delphinidae family, which exhibit elevated energetic demands and are thus dependent on productivity (Mannocci et al 2014). By contrast, seabed depth, slope, and SST were not significant predictors in the final model, although sightings were largely made in intermediate depths (600-1200 m with a peak around 800 m), over steep bathymetric slopes (5-88), and in low regional temperatures (between 19-228C) (Supplementary Material, Appendix S6), in alignment with similar observations made in the Pacific and Atlantic Oceans, and the Mediterranean Sea (Ferguson et al 2006;Esteban et al 2014;Passadore et al 2014). Contrary to this study, the presence-only models developed by Jones et al (2019) identified depth as the most important predictor of habitat suitability, resulting in model predictions that largely (.70%) favoured flatter, more homogeneous areas between canyon heads, against the authors' own expectations.…”
Section: Discussionsupporting
confidence: 76%
“…Our modelling of killer whale relative density indicated a positive relationship with maximum Chl a concentration, consistent with the known physiology of other members of the Delphinidae family, which exhibit elevated energetic demands and are thus dependent on productivity (Mannocci et al 2014). By contrast, seabed depth, slope, and SST were not significant predictors in the final model, although sightings were largely made in intermediate depths (600-1200 m with a peak around 800 m), over steep bathymetric slopes (5-88), and in low regional temperatures (between 19-228C) (Supplementary Material, Appendix S6), in alignment with similar observations made in the Pacific and Atlantic Oceans, and the Mediterranean Sea (Ferguson et al 2006;Esteban et al 2014;Passadore et al 2014). Contrary to this study, the presence-only models developed by Jones et al (2019) identified depth as the most important predictor of habitat suitability, resulting in model predictions that largely (.70%) favoured flatter, more homogeneous areas between canyon heads, against the authors' own expectations.…”
Section: Discussionsupporting
confidence: 76%
“…This area is characterized by the confluence of two water masses with contrasting features: the warm Brazil Current and the cold Malvinas/Falkland Current. In addition to this water-mixing process, discharges from the Rio de la Plata make the Subtropical Convergence Zone a highly productive ecosystem with capacity to sustain high trophic levels (sharks, tunas, seabirds, sea turtles, and marine mammals) (Acha et al, 2004;Domingo et al, 2009;Jiménez et al, 2011;Pons and Domingo, 2013;Passadore et al, 2014;Gaube et al, 2017). The reasons for these horizontal movements are not entirely known but may suggest an ability to discriminate among areas of particular significance for foraging or reproduction purposes (Heupel et al, 2007;Petersen et al, 2007;Block et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The fishing effort was calculated as the total number of hooks hauled during a fishing day. Both operational variables were tested under the assumption that increased fishing effort and spatial spread of effort would increase the probability for killer whales to detect and to converge on fishing gear, therefore increasing the probability of interaction ( Passadore et al, 2014 ; Cruz et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%